(untitled) (Collection of scientific works «Modern structures of metal and wood», 2024)
Quite often, underground tanks designed to store liquid materials lose their operational suitability in a short period of operation in real conditions. The largest number of defects is associated with the loss of tank shell local resistance. It was carried out the stress-strain state analysis for a typical tank with a volume of 75.0 m 3 made of a cylindrical two-layer shell. There are determined the reasons for the local stability loss of the shells and the corresponding recommendations are given. The purpose of the paper is to determine the tank’s stress-deformation state to identify the causes of deformations of the casing and to provide appropriate recommendations for its strengthening. It works in real operating conditions by the actual loading. The main load on the underground tank is the external pressure of the soil. The calculation of the tank is performed as for a horizontal cylindrical shell with elliptical sidewalls under the action of external pressure.